DNA Damage in Working Individuals Occupationally Exposed to Cooking Oil Fumes Using Peripheral Blood Comet Assay - Chaudhary, Aditi; Pappuswamy, Manikantan (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Cooking oil fumes (COFs) endorses major genetic changes in human health by endorsing physical stress, which plays an important role in producing physiological and genetic alterations. COFs combined with smoking habits provide a significant risk that exacerbates genetic changes. The DNA damage was assessed in the current investigation utilizing a blood cell comet test on 30 desk job employees of companies who were occupationally exposed to COFs and 30 healthy persons. Only the experimental individuals were categorized as smokers or nonsmokers depending on the duration of their exposure. The Student's t-test was used to assess the data statistically. The DNA damage percentage of smoking experimental was observed to be 10.2±0.3% that is much elevated to the 7.1±0.2% in control smokers participants of 31-35 years of age. The investigation's findings showed that there was copious DNA damage among the workers. Office workers who smoke cigarettes collectively cause more DNA damage than they prevent.